Spatial assessment and appraisal of groundwater suitability for drinking consumption in Andasa watershed using water quality index (WQI) and GIS techniques: Blue Nile Basin, Northwestern Ethiopia. Issue 1 (1st January 2020) - Bawoke, Getnet Taye; Anteneh, Zelalem Leyew
Abstract: This study aimed to evaluate the overall groundwater hydrogeochemical evolution and suitability for drinking in Andasa watershed (Northwestern Ethiopia). To achieve this, analyses of hydrogeochemical, multivariate (PCA, HCA), correlation matrix, and Water Quality Index (WQI) methodologies were employed. A total of 64 groundwater samples which had been collected during winter season (February–April, 2018) were assessed for ionic and composite variables (major physicochemical and composite parameters). The samples have been gathered from deep wells, shallow wells, hand dug wells and springs which are spatially distributed throughout the watershed. The study results revealed that major ions dominating are Ca>Mg>Na>K and HCO3 > Cl>SO4 > NO3 > PO4  > F for cations and anions, respectively. Ca-HCO3, Mg-Ca-HCO3 -Cl, Mg-Ca-Na-HCO3 -SO4, Mg-HCO3 -SO4, Mixed CaMgHCO3, Mixed CaNaHCO3 and Na-HCO3 were recognized as water types where Ca-HCO3 (59.69%) was identified as dominant. Ionic ratio plots are indications for groundwater enrichment by Na +, Ca 2+ and Mg 2+ cations (silicate minerals hydrolysis). Chloro-alkaline indices resulted for CAI-I (96.88%) and CAI-II (84.48%), showed Ca 2+ +Mg 2+ exchange in groundwater with Na + +K + in an aquifer, confirmed for cation exchanging. Four factor loadings (PCA analysis) explained for the existence of geogenic and anthropogenic pollutions. WQI values showed the majority of the samples comprised "good water" (57.81%), distributed in southern and western parts, followed by "excellent water" (20.31%). Additionally, WQI maps portrayed "Good" to "poor water" types in northern portions (waste disposal landfill, urban centers, irrigated areas), while "very poor" to "unsuitable" types are dispersed to northeastern tips. Generally, the study result is believed to give directions for groundwater management options.